The Effect of Perception of Ease of Use, Benefits, Sustainability Risk, and Online Customer Service Quality on Continuation Intention to Use QRIS in the DIY Community - Zalfaa Nabiilah Safitri; Citra Ayudiati (Universitas KH. Abdul Chalim Mojokerto, 2025)
It is crucial to comprehend the reasons impacting the continuous usage of digital payment systems, especially the Indonesian Quick Response Code (QRIS) in the Special Region of Yogyakarta (DIY), given their rapid expansion. Although QRIS adoption and its effects on SMEs have been studied in the past, there are currently few thorough studies that integrate the influence of perceived benefits, simplicity of use, sustainability risks, and the caliber of online customer support from the viewpoint of the consumer. The purpose of this study is to examine and evaluate how each independent variable affects the DIY community's intention to keep using QRIS. Using a quantitative methodology, this study gathers primary data using a questionnaire survey. SmartPLS 4 software was then used to analyze the data using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). In this investigation, the structural model (inner model) for hypothesis testing and the measurement model (outer model) for validity and reliability were assessed. The findings indicate that although QRIS has been widely used, users' intentions to stick with it are not significantly influenced by perceived sustainability risks, perceived advantages, or perceived ease of use. Nonetheless, the intention to stick with QRIS is strongly influenced by the caliber of online customer support. This implies that, in addition to the factors that initially influenced adoption, sustaining user engagement and promoting long-term QRIS adoption depend heavily on efficient, dependable, and responsive customer assistance. Therefore, in order to guarantee client loyalty and the ongoing use of digital payment technologies, service providers had to give top priority to enhancing online customer care.